Improving the Performance of Holter ECG Monitor with Digital Filter Comparison Method for Motion Artifact Reduction - TOAN, HELENORA; Luthfiyah, Sari (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
Holter ECG monitor is a device that records the patient's heart activity throughout the day, but the patient's body movements can cause artifacts that interfere with ECG signal quality. This study aims to improve the performance of Holter Monitor by comparing Infinite Impulse Response (IIR) and Finite Impulse Response (FIR) filters in reducing motion artifacts. Filters were applied at various orders using Butterworth and Window methods. Analysis was performed with Fast Fourier Transform (FFT) to evaluate the effectiveness of the filters in reducing artifacts. The results show that digital filters significantly reduce motion artifacts. FIR filters at high orders (6 and 8) provide a more stable signal with an average SNR value of 10.3282 at order 8. While the IIR filters at low orders (2 and 4) with an average SNR of 12.0281 at order 2, reduced the artifacts well, but at high orders were unstable and resulted in signal distortion. This research is expected to assist medical personnel in analyzing better heart signal data and improve the quality of portable heart monitoring for patients undergoing daily activities, while enabling more efficient data transmission without removing the SD Card.